2011
DOI: 10.5511/plantbiotechnology.11.0725a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the ozone tolerance of poplar plants with an antisense DNA for 1-aminocyclopropane-1-carboxylate synthase

Abstract: Genetically transformed lombardy poplar (Populus nigra L. var. italica Koehne) were regenerated after the cocultivation of stem segments with Agrobacterium tumefaciens strain LBA4404, which harbored a binary vector that included an antisense DNA for ozone-inducible 1-aminocyclopropane-1-carboxylate (ACC) synthase from poplar leaves. Lower rates of ozone-induced ethylene production were observed in transgenic plants than in wild-type plants. Ozoneinduced visible damage was attenuated in these lines, and the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thus, the evidence that enhanced isoprenoid emissions could improve plant O 3 tolerance is mixed. Blocking ethylene biosynthesis following O 3 exposure by reducing expression of 1‐aminocyclopropane‐1‐carboxylate (ACC) synthase (ACS) has been shown to improve O 3 tolerance in N. tabacum and poplar (Nakajima et al ., ; Mohri et al ., ), but has not been tested in more widely grown crop species. Another transgenic strategy to enhance ROS scavenging is to alter the amount and activity of enzymes that supply or reduce ascorbate in the apoplast (Conklin and Barth, ).…”
Section: Efforts To Map or Engineer Crop Tolerance To Ozonementioning
confidence: 99%
“…Thus, the evidence that enhanced isoprenoid emissions could improve plant O 3 tolerance is mixed. Blocking ethylene biosynthesis following O 3 exposure by reducing expression of 1‐aminocyclopropane‐1‐carboxylate (ACC) synthase (ACS) has been shown to improve O 3 tolerance in N. tabacum and poplar (Nakajima et al ., ; Mohri et al ., ), but has not been tested in more widely grown crop species. Another transgenic strategy to enhance ROS scavenging is to alter the amount and activity of enzymes that supply or reduce ascorbate in the apoplast (Conklin and Barth, ).…”
Section: Efforts To Map or Engineer Crop Tolerance To Ozonementioning
confidence: 99%
“…In cotton, a variety of ACSs exhibited enhanced expression leveles in the presence of salinity, irrespective of the duration of exposure (Peng, 2014). In poplar, down-regulation of one ACS homolous gene (ACS1) is effctive in enhancing the tolerance to salt stress by the introduction of its antisense DNA (Nobuyoshi, 2014). Other results showed that the expression of VrACS1, VrACS6 and TaACS6, TaACS9, ACS homologous genes in Vigna radiata (mung bean) and wheat, could be also signi cantly induced after salt stress treatment (Cheng, 2008;Song, 2001).…”
Section: Introductionmentioning
confidence: 99%